Soluble T cell receptor-based immunotherapies empowered by large scale HLA ligandomics. (October 2022) - Capuano, F.; Mommen, G.P.M; Carreira, R.J; Lowne, D.; Cundell, M.J.; Powlesland, A.S.
Abstract : Objectives: Immunocore focuses on the development of T cell receptor (TCR)-based bispecifics for immunotherapy. Soluble, affinity-enhanced, TCR-based molecules are engineered to target peptides presented on the cell surface in complex with Human Leucocyte Antigen (HLA) molecules (peptide:HLA). Essential to our platform is the identification and validation of peptide:HLA targets, achieved by mass spectrometry (MS). We have particularly focussed on characterizing the immunopeptidome of the most frequent allele, HLA-A*02:01. Methods: HLA complexes are isolated from immortalized cancer cells and tumour tissues by affinity purification using various HLA-restriction specific antibodies. HLA peptides, eluted under acidic conditions, are fractionated by reverse phase liquid chromatography and analysed by LC-MS/MS. Mass spectra, searched using PEAKS, are integrated with gene expression and HLA typing data in an in-house database. Fully validated target peptides are used to clonally expand HLA-peptide specific T cells. Isolated TCRs are engineered into soluble molecules (mTCRs) whose affinity is enhanced using phage display technology. Results: Our HLA peptidomic workflow combines novel biochemical techniques with high resolution mass spectrometry and extensive data integration to maximise the depth of the HLA ligandome. Our combined findings across hundreds of cancer cell lines provides peptide information on all protein coding genes, with the very low novelty rate observed in tissue material suggesting that the processing machinery of in vitro model systems accurately represent the tissue environment. Our Immune mobilising monoclonal T cell receptors Against Cancer molecules (ImmTAC®) are generated by coupling high-affinity mTCRs with an anti-CD3 scFv domain to redirect polyclonal T cell responses toward cancer cells. Immunocore has three ImmTAC molecules in clinical trials with our lead candidate, IMCgp100, entered in pivotal trials as a monotherapy for the treatment of patients with metastatic uveal melanoma (NCT03070392, clinicaltrials.gov). Conclusions: Our cell line-based HLA-A*02:01peptide atlas represents a comprehensive resource for effective design of TCR-based immunotherapeutics for cancer treatment.